PERSPEKTIF KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN TANGGUNG JAWAB SOSIAL SEBAGAI VARIABEL MODERASI - Bhinuko, Ary; Setyorini Gunawan, Diah; Geraldina, Ira (Jurnal GeoEkonomi, 2025)
This study aims to analyze the impact of firm value, profitability, and Corporate Social Responsibility (CSR) on company performance, particularly from the perspective of creditors. Firm value is often used to assess a company's ability to manage financial obligations, such as repaying loans to creditors. In this regard, company liquidity becomes an important indicator in determining the extent to which a company can meet its obligations. Additionally, profitability, which measures a company's ability to generate profit, is also considered an important factor in assessing company performance and stability. Previous studies have shown varying results regarding the impact of profitability on firm value, with some studies reporting a positive impact and others a negative one. Corporate Social Responsibility (CSR) also plays a significant role in improving the company's image and facilitating sustainable development, which can contribute to long-term company performance. Based on the research findings and discussions regarding the impact of liquidity, profitability, firm value, and the influence of corporate social responsibility on coal mining companies in Indonesia, this study is expected to provide insights into company performance as seen through DER (Debt to Equity Ratio) and ROA (Return on Assets). This research also aims to provide insights regarding the impact of CSR, which has not yet been able to moderate the effects of liquidity and profitability on firm value. Keywords: Virm Value, Profitability, Debt Policy, Corporate Social Responsibility